Concurrent diabetes and heart failure: interplay and novel therapeutic approaches. Issue 3 (20th May 2021) - Karwi, Qutuba G; Ho, Kim L; Pherwani, Simran; Ketema, Ezra B; Sun, Qiuyu; Lopaschuk, Gary D
Abstract: Diabetes mellitus increases the risk of developing heart failure, and the co-existence of both diseases worsens cardiovascular outcomes, hospitalization, and the progression of heart failure. Despite current advancements on therapeutic strategies to manage hyperglycaemia, the likelihood of developing diabetes-induced heart failure is still significant, especially with the accelerating global prevalence of diabetes and an ageing population. This raises the likelihood of other contributing mechanisms beyond hyperglycaemia in predisposing diabetic patients to cardiovascular disease risk. There has been considerable interest in understanding the alterations in cardiac structure and function in diabetic patients, collectively termed as 'diabetic cardiomyopathy'. However, the factors that contribute to the development of diabetic cardiomyopathies are not fully understood. This review summarizes the main characteristics of diabetic cardiomyopathies, and the basic mechanisms that contribute to its occurrence. This includes perturbations in insulin resistance, fuel preference, reactive oxygen species generation, inflammation, cell death pathways, neurohormonal mechanisms, advanced glycated end-products accumulation, lipotoxicity, glucotoxicity, and post-translational modifications in the heart of the diabetic. This review also discusses the impact of antihyperglycaemic therapies on the development of heart failure, as well as how current heart failure therapies influence glycaemic control in diabetic patients. We also highlight the current knowledge gaps in understanding how diabetes induces heart failure.